Еволюція інструментів підтримки транскордонної співпраці у Європі - Карпчук, Н. П.; Karpchuk, N.P. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The article focuses on the development of instruments for cross-border cooperation legal support. The survey covers the period from spontaneous forms of cross-border cooperation up to the elaboration of powerful documents for financial support and spread of the cross-border cooperation initiatives.
Evolution of the Instruments for the Support of Cross-border Cooperation in Europe
Н.П. Карпчук, к.філол.н., доц. кафедри міжнародної інформації Східноєвропейського національного університету імені Лесі Українки (Україна, м. Луцьк)
Keywords: cross-border cooperation; Madrid Convention; communication «Wider Europe»